ISLAMIC CONSUMER BEHAVIOR: A BIBLIOMETRIC APPROACH - Afif Zaerofi (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2022)
Purpose: This study investigates the characteristics of Islamic Consumer Behavior (ICB) articles published in the Scopus-indexed journals between the year 2001 and 2020.Methods: The data was collected from Scopus-indexed and Conference articles between the year 2001 and 2020. To obtain the data, publish and perish application was employed. The articles were filtered by using the key word “Islamic Consumer Behavior”. This study was descriptive quantitative in nature and used the bibliometric approach. To analyse the data, the VOSviewer software was employed.Findings: During 20 years, 142 articles on Islamic consumer behavior were published. The number of publications fluctuated, it increased significantly in 2012, decreased from 10 to 30% between 2013 and 2018 but almost doubled in 2019 and 2020.  Based on co-occurrence analysis to 47 keywords of 142 publications, it is evident that there are 5 clusters with the keywords; 1). product, 2). religiosity, 3). model, 4). intention, and 5). value as the most frequent keywords in each cluster. It is also found that between the year 2016 and 2018, there were a shift in the topics from theory and model in 2016, customer relationship in 2017 and loyalty and halal product in 2018. Journal of Islamic Marketing was found dominantly publisher on Islamic consumer behaviors with 56 articles Amin was the most productive and impactful author. Originality: This study, by employing bibliographic aproach, contributes to the development of ICB theories.